2017
DOI: 10.3758/s13421-017-0702-7
|View full text |Cite
|
Sign up to set email alerts
|

Do actions speak louder than words? Examining children’s ability to follow instructions

Abstract: The ability to encode, retain, and implement instructions within working memory is central to many behaviours, including classroom activities which underpin learning. The three experiments presented here explored how action—planned, enacted, and observed—impacted 6- to 10-year-old’s ability to follow instructions. Experiment 1 (N = 81) found enacted recall was superior to verbal recall, but self-enactment at encoding had a negative effect on enacted recall and verbal recall. In contrast, observation of other-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(91 citation statements)
references
References 62 publications
9
82
0
Order By: Relevance
“…This observation of positive encoding-enactment effects, which are particularly prevalent with verbal (rather than enacted) recall, has also been observed in children (Jaroslawska, Gathercole, Allen, & Holmes, 2016;Waterman et al, 2017, Experiment 3). One suggested mechanism for this finding is that selfenactment at encoding encourages non-strategic, automatic engagement with additional visuo-spatial and motoric codes that facilitate verbal recall (Waterman et al, 2017). This is consistent with the reduced influence of self-enactment at encoding on enacted recall: where participants are already engaging with the additional forms of visuospatial-motoric coding because they are planning for physical performance of the instructions later (Allen & Waterman, 2015;Jaroslawska, Gathercole, & Holmes, 2018).…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…This observation of positive encoding-enactment effects, which are particularly prevalent with verbal (rather than enacted) recall, has also been observed in children (Jaroslawska, Gathercole, Allen, & Holmes, 2016;Waterman et al, 2017, Experiment 3). One suggested mechanism for this finding is that selfenactment at encoding encourages non-strategic, automatic engagement with additional visuo-spatial and motoric codes that facilitate verbal recall (Waterman et al, 2017). This is consistent with the reduced influence of self-enactment at encoding on enacted recall: where participants are already engaging with the additional forms of visuospatial-motoric coding because they are planning for physical performance of the instructions later (Allen & Waterman, 2015;Jaroslawska, Gathercole, & Holmes, 2018).…”
Section: Introductionsupporting
confidence: 64%
“…Demonstration has also recently been explored in the context of working memory. Waterman et al (2017) found that having the experimenter provide visual demonstration alongside verbal presentation benefited children's memory for instructions (see also Wojcik, Allen, Brown, & Souchay, 2011) to an equivalent extent for verbal and enacted recall. Yang, Allen, Yu, and Chan (2016b) extended this to the use of video demonstration (see also Yang, Jia, Zheng, Allen, & Ye, 2018) finding that this facilitated adults' recall performance, compared to auditory presentation of verbal instruction sequences.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The following tasks have been used extensively in the literature as measures of simple and complex working memory (e.g., Berry et al, 2018;Gathercole, Pickering, Ambridge, & Wearing, 2004;Waterman et al, 2017).…”
Section: Working Memory Measuresmentioning
confidence: 99%
“…During retrieval, recall by physical action substantially improves recall accuracy relative to spoken repetition (Allen & Waterman, 2015;Gathercole et al, 2008;Jaroslawska, Gathercole, Allen, et al, 2016a;Koriat, Ben-Zur, & Nussbaum, 1990;Yang et al, 2014). These action-based effects have been found in FI studies with healthy populations (Allen & Waterman, 2015;Gathercole et al, 2008;Waterman et al, 2017;Yang et al, 2014;Yang et al, 2016) and clinical groups with lower working memory capacity (Charlesworth, Allen, Morson, Burn, & Souchay, 2014;Lui et al, 2017;Wojcik et al, 2011;Yang, Allen, Holmes, & Chan, 2017). Such effects indicate a superiority of action/visual-motor-based representations relative to verbalonly storage.…”
mentioning
confidence: 69%